Effect of Using Ginger Roots Powder and Pure Allicin in Fattening Awassi Lambs Rations on Productive Performance and the Accessory Cut Parts of Carcasses (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research has been conducted to investigate the effect of ginger roots powder with allicin in the fattening of Awassi lambs rations with its effect on productive traits as well as the secondary cuts parts of carcasses.A total number of 28 Awassi lambs were used in the research , those lambs were randomly distributed into 7 treatments, lambs fed on 4 experimental rations as follows the first ration was concentrated ration without any supplement (control), the second ration supplemented with 3.0 kg/ton of allicin, the third ration supplemented with 2.0 kg/ton ginger powder, the fourth ration supplemented with a combination of allicin (1.5 kg /ton) and ginger powder (1.0 kg/ton).Lambs fed by group feeding along with the experiment which had been lasted 91 days.The productive traits were studied such as a daily and total weight gain as well as feed conversion ratio and the consumed quantity of concentrated and rough feed.Twenty-one lambs were slaughtered (three lambs for each treatment)  to study the secondary cuts parts of the carcasses.Results revealed no significant differences among treatments in the initial and final weights and daily and total weight gains. There were no significant differences in the consumed feed among treatments and feed conversion ratio.Results indicated also nonsignificant differences in weights of the head among treatments. Meanwhile, there were significant differences (P